2019
DOI: 10.1021/acsami.9b12235
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Controlled Design of Metallic Nanocomposites

Abstract: Achieving the theoretical strength of a metallic alloy material is a demanding task that usually requires utilizing one or more of the well-established routes: i. decreasing the grain size to stop or slow down the dislocation mobility, ii. adding external barriers to dislocation pathways, iii.altering the crystal structure, or iv. combining two of the previous discrete strategies, i.e., implementing crystal seeds into an amorphous matrix. Each of the outlined methods has clear limitations, hence further improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The crystalline nanolayers interacted intensely in the confined layer-space below 10 nm, which might induce phase transformation and the formation of near-coherent interfaces. 12 8c). 153 The reported multiple-sandwiched architecture had a more coarsely grained austenitic interior and an SNDP-CC surface comprising alternating austenite and martensite nanolayers with thicknesses of 5−7 nm.…”
Section: Mechanicalmentioning
confidence: 97%
See 4 more Smart Citations
“…The crystalline nanolayers interacted intensely in the confined layer-space below 10 nm, which might induce phase transformation and the formation of near-coherent interfaces. 12 8c). 153 The reported multiple-sandwiched architecture had a more coarsely grained austenitic interior and an SNDP-CC surface comprising alternating austenite and martensite nanolayers with thicknesses of 5−7 nm.…”
Section: Mechanicalmentioning
confidence: 97%
“…148−151 The distinct crystalline phases constituting the SNDP-CC alloys with different crystallographic structures or orientations facilitate phase-transformation-induced strengthening in the confined nanoscale space through the release of deformation energy. 12 Therefore, interfacial compatibility and phase stability play significant roles in the deformation behavior of SNDP-CC materials. Xin et al reported an SNDP-CC magnesium alloy obtained via ultrafast spinodal decomposition at a low temperature (Figure 8a).…”
Section: Mechanicalmentioning
confidence: 99%
See 3 more Smart Citations